Empowerment of Business Actors For Halal Certification In Kaliwates District, Jember Regency - Mohammad Wildan Habibi (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose – This community engagement research aims to increase entrepreneur understanding of the importance of halal certification, provide practical assistance in document preparation and certification prosedures, and foster synergy among lectures, students, and relevant institutions in supporting the development of halal ecosystem. Design/methodology/approach – The study employed an Asset-Based Community Development (ABCD) approach, involving 25 food and processed product enterprises as participants. Data were collected through observation, interviews, and cocumentation, and analyzed using a descriptive qualitative method. Findings – The findings indicate a significant improvement in bussines actors awaranes and readiness ro apply for halal certication. Originality/value – The collaborative mentoring model based on the ABCD approach is effective in accelerating the adoption of halal certification and fostering a sustainable local halal ecosystem.